AYURVEDIC MANAGEMENT OF SECONDARY INFERTILITY DUE TO POLYCYSTIC OVARIAN SYNDROME AND TUBAL BLOCK: A CASE STUDY (International Journal of Ayurveda and Pharma Research, 2021)
Secondary infertility is defined as the inability of a couple to conceive who had at least one prior conception. Ovarian factor and tubal factor are the most frequent causes of secondary infertility in woman. Polycystic Ovarian Syndrome is a common endocrinological disorder and it is characterized by menstrual irregularities and anovulation. It can be correlated with Nashtartava in Ayurveda. Tubal factor infertility occurs when an obstruction in fallopian tube and it can be correlated with Sanga srotodushti of Artavavaha srotas or Beejavaha srotas. A 36 year old female presented with a complaint of secondary infertility a diagnosed case of Polycystic Ovarian Syndrome and tubal block with a history of neonatal death due to preterm delivery at 24 week gestation and husband aged 38 year with normal semen analysis. The present case was treated on Ayurvedic management protocol including shodhana, samana therapies and uttaravasti. Treatment was started with Deepana - Pachana medicines. Then Udwarthanam, Virechanam, Mathra vasti and Uttaravasti were done which removes the srotorodha and helps in proper formation of each dhatu. Uttaravasti is the most effective local treatment in gynaecological disorders. Uttaravasti with hot potency medicine is very effective in treating tubal blockage. The outcome of the treatment resulted in twin pregnancy and delivered two female babies. So the present case signifies the fruitful outcome of Ayurvedic treatment in the field of infertility.   Keywords:  Secondary infertility, Polycystic Ovarian Syndrome, Tubal block, Nashtartava, Artavavaha srotas, Uttaravasti